2002
DOI: 10.1124/dmd.30.7.763
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transport of Irinotecan in Caco-2 Cells and MDCK II Cells Overexpressing Efflux Transporters Pgp, cMOAT, and MRP1

Abstract: ABSTRACT:Irinotecan (CPT-11) is a water-soluble camptothecin (CPT) derivative that has been recently approved in the United States for patients as a first-line therapy in advanced colorectal cancer. Phase I clinical trials using oral CPT-11 have shown poor and variable oral bioavailability. The present study was designed to investigate the intestinal absorption and efflux mechanisms of CPT-11 using in vitro cell culture models, Caco-2 cells, and engineered MadineDarby canine kidney (MDCK) II cells overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 25 publications
2
42
0
2
Order By: Relevance
“…This is in accord with previous reports showing similar results with topotecan (de Vries et al, 2007;Sharom, 2008). Other camptothecin analogs have also been shown to be substrates of BCRP, which was reported to transport irinotecan, SN-38, and SN-38 glucuronide (Maliepaard et al, 1999;Nakatomi et al, 2001;Luo et al, 2002). Our studies also showed that AR-67 carboxylate is transported by OATP1B1 and OATP1B3 (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in accord with previous reports showing similar results with topotecan (de Vries et al, 2007;Sharom, 2008). Other camptothecin analogs have also been shown to be substrates of BCRP, which was reported to transport irinotecan, SN-38, and SN-38 glucuronide (Maliepaard et al, 1999;Nakatomi et al, 2001;Luo et al, 2002). Our studies also showed that AR-67 carboxylate is transported by OATP1B1 and OATP1B3 (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Topotecan and the active irinotecan metabolite SN-38 (7-ethyl-10-hydroxy-camptothecin) have been identified as breast cancer resistance protein (BCRP) substrates de Vries et al, 2007) whereas transport mediated by multidrug resistant protein 1 (MDR1) has been reported for topotecan and irinotecan (Luo et al, 2002;de Vries et al, 2007). Notably, expression of BCRP in established cancer cell lines and tumor biopsy samples has been associated with resistance to camptothecins Candeil et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(11) Efflux of the parent compound and metabolites out of cells by several other transporters (e.g., ABCG2, ABCC1) also occurs. (12,13) Liver uptake transporters might also be involved in the disposition of irinotecan and its metabolites. (14) Investigators have uncovered some genetic sources of variation in the drug's pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…MRP2 is expressed in many solid human tumors originating from kidney, colon, breast, lung, and ovary (Sandusky et al, 2002), and it was shown that the protein actively transports many types of anticancer and other drugs like vinca alkaloids, anthracyclines, protease inhibitors, antibiotics, etoposide, cisplatin, methotrexate, and irinotecan in vitro (Bakos et al, 2000;Borst and Oude Elferink, 2002;Luo et al, 2002;Chan et al, 2004). Mrp2 is involved in vivo in the excretion of methotrexate and irinotecan and its metabolites into the bile, as was demonstrated in Mrp2-deficient rats (Chu et al, 1997;Masuda et al, 1997).…”
mentioning
confidence: 99%